Supplementing regular training with short-duration sprint-agility training leads to a substantial increase in repeated sprint-agility performance with national level badminton players - Walklate, B. M.; O'Brien, B. J.; Paton, C. D.; Young, W. (The Journal of Strength and Conditioning Research, 2009)
Repeated-agility sprint ability is an important performance characteristic of badminton players. However, it is unclear whether regular badminton training is sufficient to improve repeated-agility sprint ability or whether supplementary training is required. Therefore, our aim was to investigate whether supplementing regular group training with short sessions of badminton-specific agility-sprint training conferred any greater changes in performance than regular training alone. Twelve national level badminton players completed a set of performance tests in the week before and after a 4-week training period. Performance tests consisted of 10- and 20-meter sprints, a multistage fitness test, a 300-meter shuttle run, and a novel badminton sprint protocol. After pretesting, pair-matched participants were randomly assigned into regular or supplementary training groups. Both groups undertook regular national squad training consisting of 4 2-hour sessions per week. In addition, the supplementary group completed a high-intensity sprint-training regime consisting of 7 to 15 repeats of badminton-specific sprints twice per week. Relative to control, the supplementary training group reported improvements (mean ± 90% confidence limits) in the 300-meter shuttle run (2.4% ± 2.7%) and badminton sprint protocol (3.6% ± 2.6%). However, there were no substantial difference in either the 10-meter (-0.3% ± 2.1%) or 20-meter (-0.6% ± 1.8%) sprint or the multistage fitness test (0.0% ± 2.7%). Supplementing regular training with sessions of short-duration sprint training appears to lead to worthwhile increases in repeated-agility sprint performance with national level badminton players.